Risk management in projects: peculiarities of Lithuanian construction companies - Banaitienė, Nerija; Banaitis, Audrius; Norkus, Artūras (International Journal of Strategic Property Management, 2011)
Risk analysis and management is nowadays a critical factor to successful construction project management, as construction projects tend to be more complex, dynamic, always unique, and competition increasingly tougher. risk management helps the project participants—client, contractor or developer, consultant, and supplier—to meet their commitments and minimize negative impacts on construction project scope, cost, schedule (and quality, as a Result). The benefits of the risk management process include identifying and analyzing risks, and improvement of construction project management processes and effective use of resources. This paper reports the research that aims to discover how construction companies perceive the significance of the construction projects risks they face and the extent to which they employ potential risk responses.First Publish Online: 14 Apr 2011